The Use of Sound Recorders to Remotely Measure Grass Intake Behaviour in Horses - Daisy E. F. Taylor; Bryony E. Lancaster; Andrea D. Ellis (Animals)
Visual observation to record grass intake is time-consuming and labour-intensive. Technological methods, such as activity monitors, have been used but only record head position. This study aimed to evaluate sound recorders attached to headcollars to acoustically measure grass intake behaviour in horses as a low-cost alternative method. Pilot Study 1 assessed 6 × 11 min periods comparing bites/min and chews/min between video footage (VD) and sound recorders (SR). Grazing was identified audibly (SRear) and visually through soundwave pattern software (SRwav). Chew rates (SRear: 47 ± 5 chews/min, VD: 43 ± 4 chews/min) were similar between methods. Pilot Study 2 compared hourly grass intake times between SRwav and visual observation (VO) for two horses during a 3 h period. Results showed significant correlation between methods (rho = 0.99, p < 0.01, Spearman). The main study measured intake behaviour using SRwav and VO methods for three free-ranging horses during 3 h observation periods over multiple days, adding up to 3 × 24 h in winter and in spring (n = 48). Mean differences per period between SRwav and VO were 1.8% ± 3 s.d. Foraging duration per period measured with SRwav closely matched VO (r2 = 0.99, p < 0.001). Sound recorders accurately recorded grass intake time and chews in grazing horses during moderate weather conditions.